Existentialism in Samuel Beckett's Act Without Word: a Thematic Study (مجلة ديالى للبحوث الانسانية, 2022)
Samuel Beckett is one of Existentialism significant establishers. He tries throughout his plays to represent the meaning of absurd theatre accurately as “out of harmony” as it originally means in music. The study consists of five sections. It starts with the introduction and methodology. Second section is an overview of the Theatre of the Absurd, while the third is Samuel Beckett's life and work. The fourth section is the Analysis of the play Act without Words and its significant characteristics. The conclusion is the fifth section that sums up the findings.